Uterine Rupture During Medical Induction for Second Trimester Abortion - Poudel, Rekha; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Bajracharya, Nishma; Tiwari, Kenusha; Bharati, Sonu (Journal of Nepal Health Research Council, 2020)
Medical induction is an alternative to dilatation and evacuation (D and E) in second trimester abortion, though it has higher risk of minor complications compared to D and E. Combination of mifepristone and misoprostol is commonly used for the medical abortion. A 32 years G3P2L2 with previous two cesarean delivery was referred to our center at sixteen weeks of gestation for termination of her pregnancy. After 63 doses of misoprostol, she had to undergo unintended major intra-abdominal surgery for partial uterine rupture. Keywords: Dilatation and evacuation; medical induction; second trimester abortion; uterine rupture.